Polymorphism of sheep MHC Class IIb gene TAPASIN - Siva Subramaniam, N.; Morgan, Eleanor; Lee, C.; Wetherall, John; Groth, David (ELSEVIER, 2010)
The Major Histocompatibility Complex (MHC) is one of the most gene dense regions in the genome and studies in several species have shown significant associations between the MHC and disease. The endoplasmic reticular glycoprotein, tapasin, is involved in the MHC class I antigen presentation pathway. Sheep TAPASIN is located in the class IIb region of the MHC. Sheep TAPASIN was subcloned from BAC and cosmid genomic clones and DNA sequenced. TAPASIN is 9549 bp in length and encodes a protein of 447 amino acids. The structure of sheep TAPASIN was similar to other mammals and consisted of eight exons with a distinctively larger intron between exon three and four. Sheep TAPASIN gene had high sequence identity with other mammalian TAPASINs. The TAPASIN gene sequence is conserved across many mammalian species and is possibly maintained through purifying selection with the average ratio of ds/dn of 3.9. Twenty-six SNPs in sheep TAPASIN were identified.